Growth performance of common house cricket (Acheta domesticus) and field cricket (Gryllus bimaculatus) crickets fed on agro-byproducts - Orinda, Mary Akinyi; Mosi, Reuben O.; Ayieko, Monica A.; Amimo, Fred Anangwe (JEZS, 2017)
Abstract The present study was conducted to investigate the growth performance of Acheta domesticus and Gryllus bimaculatus fed on different agro-byproducts. The experiment was carried out between February- July 2017 within Jaramogi Oginga Odinga University of Science and Technology Insect Farm. Randomized Complete Block Design was used as the experimental design with four treatments: rice bran+ blood meal (RBBM), rice bran + spent grain (RBSG), & + rice bran + spent yeast (RBSY) and Grower’s mash (GM) as the control. 100g of each feed type was provided ad libitum for a week. Mean adult weight for G. bimaculatus were 0.989±0.02g, 0.6038±0.19g, 0.7333±0.23g and 0.6758±0.22g for cohorts fed on GM, RBSY, RBBM and RBSG respectively while the mean adult weight for A. domesticus were 0.6085±0.022g, 0.3415±0.12g, 0.368±0.11g and 0.4598±0.15g for cohorts fed on GM, RBSY, RBBM and RBSG correspondingly. Both species and treatment affected growth rate of the crickets significantly (P<0.000). The results of the study indicated potentiality of agro-byproducts as a cheap source of cricket feed. By implication, the results call for evaluation of bioavailability of the ingested feed and calculation of feed conversion ratios so as to establish efficiency of the feeds.
Keywords: Agro-byproducts; Cricket; Feed; Growth Performance